1983
DOI: 10.1038/302716a0
|View full text |Cite
|
Sign up to set email alerts
|

Hamster preproglucagon contains the sequence of glucagon and two related peptides

Abstract: Glucagon is a 29-amino acid polypeptide hormone synthesized by the A cells of the endocrine pancreas. Its primary site of action is the liver where it stimulates glycogenolysis, gluconeogenesis and ketogenesis. In mammals, biosynthetic studies have shown that glucagon is derived from a precursor of molecular weight (Mr) approximately 18,000 which is five to six times larger than glucagon. Glucagon-containing polypeptides and immunoreactants of various sizes have also been described from stomach, intestine, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
235
0
5

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(242 citation statements)
references
References 32 publications
2
235
0
5
Order By: Relevance
“…This molecule contained a glucagon-like peptide (GLP) in addition to anglerfish glucagon, and therefore nurtured the notion that the proglucagon gene might encode more than one bioactive peptide. Finally, in 1983, G. Bell and co-workers cloned the hamster and human proglucagon genes [18,19] and were thereby able to deduce the human proglucagon sequence. In agreement with the prediction, its N-terminus consisted of the full sequence of glicentin, containing also the glucagon sequence.…”
Section: Discovery Of Glucagon-like Peptide-1mentioning
confidence: 99%
“…This molecule contained a glucagon-like peptide (GLP) in addition to anglerfish glucagon, and therefore nurtured the notion that the proglucagon gene might encode more than one bioactive peptide. Finally, in 1983, G. Bell and co-workers cloned the hamster and human proglucagon genes [18,19] and were thereby able to deduce the human proglucagon sequence. In agreement with the prediction, its N-terminus consisted of the full sequence of glicentin, containing also the glucagon sequence.…”
Section: Discovery Of Glucagon-like Peptide-1mentioning
confidence: 99%
“…As well as for glucagon, it also encodes for two glucagon-like peptides (GLP-1 1-37 or proglucagon sequence 72-108, and GLP-2 or proglucagon sequence 126-158) [3]. Paired basic amino acids were considered to be the enzymatic cleavage points.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon-like peptide-2 has no effect on insulin secretion at any glucose concentration tested. It is concluded that glucagon-like peptide-t, in contrast to glucagon-like peptide-2, exhibits a glucose-dependent insulinotropic action on isolated rat pancreatic islets similar to that of glucagon and gastric inhibitory polypeptide.Key words: Glucagon-like peptide-t, glucagon-like peptide-2, insulin release, glucose dependency, isolated islets.Pancreatic preproglucagon m-RNA, the precursor of pancreatic glucagon, has been cloned and sequenced from different species using recombinant DNA-techniques [1][2][3][4][5]. Two other peptides have been found arranged in tandem on the same m-RNA in close proximity C-terminal to the glucagon precursor: glucagonlike peptide-I (GLP-1) and glucagon-like peptide-2 (GLP-2) comprising 36 and 34 amino acid residues, respectively.…”
mentioning
confidence: 99%
“…Pancreatic preproglucagon m-RNA, the precursor of pancreatic glucagon, has been cloned and sequenced from different species using recombinant DNA-techniques [1][2][3][4][5]. Two other peptides have been found arranged in tandem on the same m-RNA in close proximity C-terminal to the glucagon precursor: glucagonlike peptide-I (GLP-1) and glucagon-like peptide-2 (GLP-2) comprising 36 and 34 amino acid residues, respectively.…”
mentioning
confidence: 99%